(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
This article explores the transformative role of ultrasound therapy in periodontal care, revolutionizing traditional approaches to the treatment of periodontal diseases. With its non-invasive nature and precision in calculus removal, ultrasound therapy offers an efficient and patient-friendly alternative, minimizing discomfort and treatment times. Beyond scaling, ultrasound stimulates tissue healing, accelerating postoperative recovery. The advantages of ultrasound, including reduced invasiveness and enhanced therapeutic outcomes, mark a paradigm shift in dental practices. Ongoing research and interdisciplinary collaborations hold the key to optimizing ultrasound therapy protocols, ensuring standardized and effective integration into routine periodontal care. As dental practitioners embrace this innovative modality, the future promises a holistic and personalized approach to periodontal diseases.